The hermeneutics of the biblical writers learning to interpret scripture from the prophets and apostles - Chou, Abner (Chicago Kregel Publications, 2018)
Cover Page -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Abbreviations -- Chapter 1: The Quest for Authorial Logic -- Chapter 2: Groundwork for the Quest: Presuppositions and Method -- Chapter 3: The Prophetic Hermeneutic: The Prophet as Exegete and Theologian -- Chapter 4: The Prophetic Hermeneutic: Did the Prophets Speak Better than They Knew, or Better than We Give Them Credit For? -- Chapter 5: The Apostolic Hermeneutic: Continuity with the Prophets -- Chapter 6: The Apostolic Hermeneutic: The Theological Fabric of the New Testament -- Chapter 7: The Christian Hermeneutic: Reading as They Read and Intended -- Chapter 8: Scripture's Sophistication, First Theologians, and the Hermeneutics of Surrender -- Bibliography -- Back Cover.
Description based on publisher supplied metadata and other sources
Keywords: Bible-Hermeneutics; Electronic books